Analysis of The Leading Sector of North Penajam Paser Regency 2015 – 2019 - Irfan Sofi (Direktorat Jenderal Anggaran Kementerian, Keuangan Republik Indonesia, 2020)
The Central Government has designated North Penajam Paser Regency as one of the new capital areas. The aim of the Government to move the capital city from Java Island is for equitable development and economic growth. The existence of limited regional funds requires local governments to arrange the priority of economic sectors which have to be developed in their regions. Mistakes in selecting priority sectors will cause waste of funds and underdevelopment of the regional economy. The purpose of this research is to identify and analyze the leading sectors of North Penajam Paser Regency. This research uses Location Quotient and Shift Share analysis methods with Gross Regional Domestic Product for 2015 to 2019. The results showed that the construction and real estate sectors were the leading sectors.